Scleroderma with tongue involvement. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2016)
In the child you can observe all the forms of scleroderma from localized cutaneous to systemic sclerosis; however, the localized cutaneous is the most frequent form of scleroderma and more generally of the connective tissue diseases in the child. As with other connective tissue diseases, and more generally for many other diseases, the severity is very variable and it ranges from minimal forms that require only a topical immunosuppression to very severe forms requiring systemic immunosuppression. In addition to the skin, scleroderma can also affect the mucous membranes and in particular the oral cavity; the involvement of the oral cavity, particularly of the the tongue is more common in systemic sclerosis and in severe forms of scleroderma like facial hemiatrophy. In the two cases here described the lingual involvement occurred in the presence of minor skin lesions, especially in the second case where there was a single chin lesion.